Contextualising the Teaching and Learning of Measurement within Torres Strait Islander Schools - Ewing, Bronwyn; Cooper, Thomas J.; Baturo, Annette R.; Matthews, Chris; Sun, Huayu (The Australian Journal of Indigenous Education, 2010)
Abstract A one-year mathematics project that focused on measurement was conducted with six Torres Strait Islander schools and communities. Its key focus was to contextualise the teaching and learning of measurement within the students' culture, communities and home languages. Six teachers and two teacher aides participated in the project. This paper reports on the findings from the teachers' and teacher aides' survey questionnaire used in the first Professional Development session to identify: a) teachers' experience of teaching in the Torres Strait Islands, b) teachers' beliefs about effective ways to teach Torres Strait Islander students, and c) contexualising measurement within Torres Strait Islander culture, communities and home languages. A wide range of differing levels of knowledge and understanding about how to contextualise measurement to support student learning were identified and analysed. For example, an Indigenous teacher claimed that mathematics and the environment are relational, that is, they are not discrete and in isolation from one another, rather they interconnect with mathematical ideas emerging from the environment of the Torres Strait communities.